Construction and validation of a prognostic model for colorectal cancer based on migrasome-related long non-coding RNAs - Lv, Qiang; Yang, Qingzhu; Chen, Hongsheng; Wang, Yang; Wang, Yuliuming; Hu, Xu; Liu, Ming (PeerJ, 2025)
Background Colon adenocarcinoma (COAD) is a globally prevalent and deadly malignancy of the digestive system. Recently, migrasomes have gained significant attention as important regulators of tumor cell migration and metastasis. The current research developed a highly accurate prognostic model using migrasome-related long non-coding RNAs (lncRNAs) in COAD, providing new insights for prognostic assessment and immunotherapy of COAD patients. Methods RNA sequencing data from COAD patients were acquired from The Cancer Genome Atlas Program (TCGA) database to construct a prognostic lncRNA model based on known migrasome-related genes (MRGs). The model’s predictive accuracy was then assessed using concordance index (C-index) analysis, nomograms, principal component analysis, and receiver operating characteristic curves. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were conducted to identify significant differences in biological functions and signaling pathways associated with differentially expressed genes in the high-risk subgroup. A comprehensive evaluation of the model incorporated clinical-pathological features, tumor microenvironment, and chemotherapy sensitivity. The expression levels of prognostic genes in COAD patients were validated via quantitative reverse transcription polymerase chain reaction (RT-qPCR). Furthermore, the role of LCMT1-AS1 in colorectal cancer was examined through CCK-8 assays, colony formation assays, and Transwell experiments. Results Migrasome-related lncRNAs were identified as robust prognostic predictors for COAD. Multivariate analysis revealed that the risk score derived from these lncRNAs is an independent prognostic factor for COAD. Patients in the low-risk group exhibited significantly longer overall survival (OS) compared to those in the high-risk group. Accordingly, the nomogram prediction model we developed, which integrates clinical features and risk scores, demonstrated excellent prognostic performance. In vitro experiments further showed that LCMT1-AS1 promotes the proliferation and migration of COAD cells.
Keywords: Colon adenocarcinoma; Migrasomes; LncRNA; Prognostic model